Knowledge and practice of healthcare providers and associated factors of essential newborn care in Ethiopia: a systematic review and meta-analysis - Geta Hardido, Temesgen; Atinafu Ataro, Bizuayehu; Elfios, Eshetu; Abuye, Tewodros Alemayehu; Kebede, Christian (Frontiers in Pediatrics, 2024)
Background: Preventing neonatal mortality and morbidity in developing countries such as Ethiopia requires improved practices and knowledge among healthcare providers. Several studies have been conducted in Ethiopia, but the overall level has not been estimated based on essential newborn care practices, knowledge of health care providers, and associated factors. Therefore, the objective of this review is to assess the overall practice and knowledge of essential newborn care and associated factors among healthcare providers in Ethiopia.Only articles published in English were included in this review.Medline/PubMed, Web of Science, Google Scholar, EMBASE, and CINAHL, Scopus, Ethiopian University Repository Online, and the Cochrane Library are the main databases. The review included cross-sectional studies written in English that met the inclusion requirements. Using a random-effects model, the overall practice and knowledge level was estimated. Additionally, funnel plots and Eggers' test were used to assess publication bias. STATA version 14 was used to perform all statistical analysis.Results: This review included 15 studies involving 3,210 health care providers in Ethiopia. In Ethiopia, overall health care providers had a good practice and knowledge level of essential newborn care of 57.38% [95% CI (49.56; 65.20); I2 = 95.3%, P<0.001] and 54.06% [95% CI (45.07; 63.05); I2 = 95.5%, P<0.001], respectively. Knowledge, training status, and material availability of healthcare professional were significantly associated with their practice of essential newborn care, while educational qualification and training status were significantly associated with the knowledge of healthcare providers of essential newborn care.Conclusions: Overall, 57% and 54% of healthcare providers had good ENC practices and knowledge. So, the Ethiopian government and other stakeholders should take immediate measures to improve essential neonatal care practice and knowledge among healthcare providers, and improve identified factors.